Influence of early quantitative food restriction on long bone growth at different environmental temperatures in broiler chickens - Bruno, L. D. G.; Furlan, R. L.; Malheiros, E. B.; Macari, Marcos [UNESP] (Carfax Publishing, 2000)
1. This investigation was carried out to study the influence of early quantitative food restriction (40% of ad libitum intake from 7 to 14 d of age) and environmental rearing temperature (thermoneutral, cold and hot) on long bone (tibia, femur and humerus) development in broiler chickens.2. Tibia, femur and humerus were obtained at the ages of 14, 21, 28, 35 and 42 d; and the variables studied were: length and width (mm, expressed as absolute values), bone breaking strength (kgf) and bone weight/bone length index (BW/BL, mg/mm).3. All bone variables increased with bird age. Food restriction reduced bone length and width but did not affect bone weight. High environmental rearing temperature reduced bone length and width at 42 d of age. Bone strength was not affected by environmental temperature but the calculated BW/BL index was reduced by heat exposure.4. The findings suggest that food restriction and high environmental rearing temperature reduce long bone growth; bone breaking strength was affected by bird age but not by food restriction nor rearing ambient temperature.